Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.11648/j.ajhr.20140203.13
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Distribution of Pott's Disease of the Spine among Adult Sudanese Patients in Khartoum, Sudan

Abstract: This was a cross-sectional hospital-based study conducted at Neurology Department, Shaab Teaching Hospital, Khartoum in a period of two years. The aim of the study was to determine the most affected region of the spine in adult Sudanese patients with Pott's disease. Hundred patients with clinical suspicion of spinal TB were enrolled in the study. Clinical history and examination, investigations for TB and imaging studies were performed. Midthoracic spines (T5 -T8) and lower thoracic spines (T9 -T12) were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…All our patients diagnosed as highly probable cases of TBM had a headache as their initial presenting symptoms. A study by Kumar et al 10 The results of the study conducted by Elwathiq et al 15 at Al-Shaab teaching hospital in 2014, over 2 years at 100 cases, showed that mid-thoracic spine Pott's (T5-T8) and lower thoracic spines (T9-T12) were found to be most cases in tuberculosis of the spine, in 20 of the cases (20%) upper thoracic vertebrae (T1-T4) were affected and in 12 (12%) lumbar spines, only 4 (4%) had a cervical spine involvement. The mid-thoracic spine was affected more and it could be attributed to infection from a combination of hematogenous, lymphatic, and direct invasion.…”
Section: Discussionmentioning
confidence: 99%
“…All our patients diagnosed as highly probable cases of TBM had a headache as their initial presenting symptoms. A study by Kumar et al 10 The results of the study conducted by Elwathiq et al 15 at Al-Shaab teaching hospital in 2014, over 2 years at 100 cases, showed that mid-thoracic spine Pott's (T5-T8) and lower thoracic spines (T9-T12) were found to be most cases in tuberculosis of the spine, in 20 of the cases (20%) upper thoracic vertebrae (T1-T4) were affected and in 12 (12%) lumbar spines, only 4 (4%) had a cervical spine involvement. The mid-thoracic spine was affected more and it could be attributed to infection from a combination of hematogenous, lymphatic, and direct invasion.…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ] similar results were presented where the majority were from urban areas (61/104 patients), and rural (43/104 patients). A study by Wang et al [ 22 ] was also favouring incidence of STB to be more in urban than rural but a study done by Ibrahim et al [ 23 ] showed it to be more in people living in rural areas. Since overcrowding is seen in urban areas and tuberculosis is known as the disease of overcrowding which spreads through droplet infection, the increased prevalence of the disease in urban overpopulated areas may be well explained.…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculous spine disease, commonly known as Pott's disease, continues to pose a significant health challenge globally, particularly in developing nations such as Pakistan (1,2). Characterized by its devastating effects on the thoracic and lumbar regions, spinal tuberculosis can lead to severe neurological complications, deformities, and vertebral collapse (3).…”
Section: Introductionmentioning
confidence: 99%